2006
DOI: 10.1007/s10456-006-9040-2
|View full text |Cite
|
Sign up to set email alerts
|

Human melanoma cells transplanted into zebrafish proliferate, migrate, produce melanin, form masses and stimulate angiogenesis in zebrafish

Abstract: In this research, we optimized parameters for xenotransplanting WM-266-4, a metastatic melanoma cell line, including zebrafish site and stage for transplantation, number of cells, injection method, and zebrafish incubation temperature. Melanoma cells proliferated, migrated and formed masses in vivo. We transplanted two additional cancer cell lines, SW620, a colorectal cancer cell line, and FG CAS/Crk, a pancreatic cancer cell line and these human cancers also formed masses in zebrafish. We also transplanted CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
273
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 278 publications
(290 citation statements)
references
References 28 publications
6
273
2
Order By: Relevance
“…We have also observed in preliminary studies that human cancer cells, when injected directly into the vasculature of 2-day-old zebrafish embryos, lodge in small vessels in various organs and extravasate into the surrounding tissue (Stoletov et al, 2007; Figure 3). Haldi et al (2005) using human melanoma cells reported similar results. While these initial results are encouraging, additional work needs to be done to confirm that fish and human cancer cells metastasize using the typical vascular and lymphatic routes, and that similar mechanisms known to drive these processes in mammals also operate in zebrafish.…”
Section: Future Directionssupporting
confidence: 58%
See 4 more Smart Citations
“…We have also observed in preliminary studies that human cancer cells, when injected directly into the vasculature of 2-day-old zebrafish embryos, lodge in small vessels in various organs and extravasate into the surrounding tissue (Stoletov et al, 2007; Figure 3). Haldi et al (2005) using human melanoma cells reported similar results. While these initial results are encouraging, additional work needs to be done to confirm that fish and human cancer cells metastasize using the typical vascular and lymphatic routes, and that similar mechanisms known to drive these processes in mammals also operate in zebrafish.…”
Section: Future Directionssupporting
confidence: 58%
“…Transplantation of human cancer cells into early-stage (6-48 h post-fertilization) zebrafish embryos has also revealed important information about cancer biology as reported by several groups (Haldi et al, 2005;Lee et al, 2005;Topczewska et al, 2006;Nicoli et al, 2007). The major advantage of this model is that the immune system is still immature that permits human tumor cell engraftment.…”
Section: Early Embryo Xenotransplantant Modelmentioning
confidence: 96%
See 3 more Smart Citations